Analysis of the Authority of the Substitute Notary Public in Preparing a Cooperative Establishment Deed - Virginia Puspa Dianti; Jawade Hafidz; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The main objective of cooperatives is established as regulated in Article 4 of Act No 17 of 2012 to improve the welfare of Members in particular and society in general, as well as as an inseparable part of a democratic and just national economic order. The formulation of the problem in this research is how to implement the establishment of a Cooperative deed according to Act No 17 of 2012? And does the substitute notary have the authority to make a cooperative deed? The type of research used by the author is normative legal research by examining library materials related to the authority of the substitute notary in making cooperative establishment deeds based on a qualitative approach. Sources and types of data in this study were obtained through secondary data. To obtain the necessary data, the author collects laws and regulations relating to the title that the author takes. In addition, the author can obtain information through searching books and scientific works of legal experts. In this case the Author analyzes the Authority of the Substitute Notary in Preparing the Cooperative Establishment Deed. From this research, the author obtained the following results: (1) The establishment of a Cooperative is carried out by means of a Cooperative Establishment Deed made by a Notary registered at the Ministry of Cooperatives in Indonesian. (2) Substitute Notary Public can also make a Cooperative Deed of Establishment as long as the Substitute Notary is registered with the Ministry that administers Government affairs in the field of cooperatives.